Saccharomyces cerevisiae Differential Functionalization of Presumed ScALT1 and ScALT2 Alanine Transaminases Has Been Driven by Diversification of Pyridoxal Phosphate Interactions - Rojas-Ortega, Erendira; Aguirre-López, Beatriz; Reyes-Vivas, Horacio; González-Andrade, Martín; Campero-Basaldúa, Jose C.; Pardo, Juan P.; González, Alicia (Frontiers in Microbiology, 2018)
Saccharomyces cerevisiae arose from an interspecies hybridization (allopolyploidization), followed by Whole Genome Duplication. Diversification analysis of ScAlt1/ScAlt2 indicated that while ScAlt1 is an alanine transaminase, ScAlt2 lost this activity, constituting an example in which one of the members of the gene pair lacks the apparent ancestral physiological role. This paper analyzes structural organization and pyridoxal phosphate (PLP) binding properties of ScAlt1 and ScAlt2 indicating functional diversification could have determined loss of ScAlt2 alanine transaminase activity and thus its role in alanine metabolism. It was found that ScAlt1 and ScAlt2 are dimeric enzymes harbouring 67% identity and intact conservation of the catalytic residues, with very similar structures. However, tertiary structure analysis indicated that ScAlt2 has a more open conformation than that of ScAlt1 so that under physiological conditions, while PLP interaction with ScAlt1 allows the formation of two tautomeric PLP isomers (enolimine and ketoenamine) ScAlt2 preferentially forms the ketoenamine PLP tautomer, indicating a modified polarity of the active sites which affect the interaction of PLP with these proteins, that could result in lack of alanine transaminase activity in ScAlt2. The fact that ScAlt2 forms a catalytically active Schiff base with PLP and its position in an independent clade in “sensu strictu” yeasts suggests this protein has a yet undiscovered physiological function.